Pengaruh Sanksi Perpajakan dan Reformasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi dengan Kebijakan Relaksasi PPh 21 sebagai Variabel Moderating - Putra, Robiur Rahmat; Julito, Kiko Armenita; Siahaan, Marta Uliana (Universitas 17 Agustus 1945 Jakarta, 2022)
This study aims to determine the effect of tax sanctions, tax administration reform on individual taxpayer compliance with the pph 21 relaxation policy as a moderating variable. The population in this study are employees. The simple random sampling method, this sampling provides equal opportunities for each population to selected to be a member of the sample. This research distributed questionnaires. This study uses SmartPLS. For this research that tax sanctions affect individual taxpayer compliance, and tax reform affects individual taxpayer compliance, but the pph 21 relaxation policy has not been able to moderate tax sanctions on individual taxpayer compliance and has not been able to moderate tax reform on mandatory compliance. personal tax.